Building downtown Los Angeles : the politics of race and place in urban America - Saito, Leland T., 1955- (Stanford University Press, 2022)
"From the 1970s on, Los Angeles was transformed into a center for entertainment, consumption, and commerce for the affluent. Mirroring the urban development trend across the nation, new construction led to the displacement of low-income and working-class racial minorities, as city officials targeted these neighborhoods for demolition in order to spur economic growth and bring in affluent residents. Responding to the displacement, there emerged a coalition of unions, community organizers, and faith-based groups advocating for policy change. In Building Downtown Los Angeles Leland Saito traces these two parallel trends through specific construction projects and the backlash they provoked. He uses these events to theorize the past and present processes of racial formation and the racialization of place, drawing new insights on the relationships between race, place, and policy. Saito brings to bear the importance of historical events on contemporary processes of gentrification and integrates the fluidity of racial categories into his analysis. He explores these forces in action, as buyers and entrepreneurs meet in the real estate marketplace, carrying with them a fraught history of exclusion and vast disparities in wealth among racial groups"--